Knowledge of breastfeeding women regarding exclusive breastfeeding in one district in Omusati region, Namibia - Veremunde Nikanor; Emma M. Nghitanwa; Monika Nakweenda (AOSIS, 2023)
Background: Breast milk is needed for the growth and development of the baby; therefore, a woman should breastfeed exclusively for six months for the baby to get all the necessary nutrients. Breastfeeding mother's knowledge on exclusive breastfeeding plays an important role in the baby's growth. Objectives: To determine and describe the knowledge of breastfeeding women regarding exclusive breastfeeding in the Outapi District, Omusati region. Methods: A quantitative, descriptive research design was used. The population were all women in nine clinics in Outapi district breastfeeding babies aged 0 to 6 months. The target population consisted of 401 lactating mothers of postnatal attendance with babies from 0-6 months in the Outapi district, in nine clinics. Cluster sampling was used to select clinic according to higher attendance, low and moderate attendance and three clinic were selected. The sample size was calculated using Solvin's formula. Simple random sampling was used to select the sample size of 200 participants. Data were collected using a self developed questionnaires that collected socio-demographic information and knowledge questions. Data was analysed using SPSS version 26. Descriptive statistics generating frequencies and percentages. Results: The results revealed that majority of the participants have knowledge regarding exclusive breastfeeding, include, the definition, the importance and advantages of breastfeeding. Most of the participants have higher knowledge on the importance of colostrum, complementary feeding as well as the importance of breastfeeding in disease prevention on the mother and the baby. The overlall knowledge of participants were higher. Conclusion: The study found out that most of the particpants are aged 20 to 31 years old, single and unemployed.The study have identified that participants have higher knowledge regarding exclusive breastfeeding. The study recommended that the Ministry of Health and Social Services (MoHSS) should institute strategies and actions that can help breastfeeding mothers to better utilize their knowledge on practicing exclusive breastfeeding and enshrined in the nutritional policy to promote health and wellbeing of new-born babies.